PELATIHAN KREATIVITAS DAN INOVASI PRODUK PATISERI BERBASIS PROBLEM BASED LEARNING - Yuriani, Yuriani; Hamidah, Siti; Palupi, Sri; Hidayah R., Nannissa (Universitas Negeri Yogyakarta, 2017)
This program was aimed at improving the independence and entrepreneurial productivity of Miftahunnajah Pesantren Al-Mumtaz Orphanage Students with creativity and innovation programs of pastry products. This training is also expected to (1) developing of the economy of the wider community by increasing the selling value of pastry products and their storage power;(2) increasing the variation of processed pastry and creating good and attractive packaging so that the students have good skill in pastry industry; and (3) improving high entrepreneurship motivation of the students. There are several obstacles faced by the students including the limitationsof capital for the development of variations of processed pastry, technological limitations in the technique of product, especially in terms of taste, processed variations and packaging, difficulties in diversifying the business, especially in the creativity and innovation of pastry products, and etc. This program provides training to students using Problem Based Learning method, by analyzing the problems faced to find alternative solutions. The methods implemented in this program include socialization, training related to the production and marketing. The result shows that some trainings and mentoring need to be done in order to improve the income of Pondok Pesantren Al Mumtaz